The power of language: The persuasiveness used in selected Philippines’ and Thailand’s tourism brochures - Myla L. Santos; Amirul Mukminin (Studies in English Language and Education, 2022)
Linguistic features of tourism brochures can describe the distinctive ways of expressing persuasiveness in advertising which have a significant impact on teaching English as a foreign or second language. This study determined how linguistic features and functions characterize the advertising stance of the Philippines’ and Thailand’s tourism brochures. It sought to explore the fundamental contributions of linguistic forms and structures in these tourism brochures to facilitate persuasiveness. A collection of tourism brochures were randomly acquired online and coded for qualitative and quantitative analyses. However, only the verbal expressions were analyzed, disregarding other components of the brochures such as semiotics. The results show that the Philippines’ and Thailand’s brochures used rhyme in their lines minimally. Most of their lines were simple narratives and descriptive statements. There were instances of neologism but no anagrammatical structure. Structural parallelism in both brochures is evident. Thailand’s brochures used minor sentences more often than the Philippines’ brochures.  Both showed a degree of informal styles. These informal styles suggested an easy-going social relationship between the audience and the advertisers. Based on the single verbs used, the Philippines’ tourism brochures capitalized on what the senses can experience and the enjoyment and satisfaction derived from such while Thailand’s tourism advertising brochures focused more on movement, both spatial and temporal. In terms of memorability, Thailand’s samples have very limited use of alliteration and metrical rhythm, while the Philippines’ samples were poetic and were fond of using alliteration.